Micro- and nanoengineered metal additively manufactured surfaces for enhanced anti-frosting applications - Zhao, Huanyu (2024)
The greater geometrical design freedom offered by additive manufacturing (AM) as compared to the conventional manufacturing method has attracted increasing interest in AM to develop innovative and complex designs for enhanced performance. However, the difference in material composition and surface properties from conventional alloys has made surface micro-/nanostructuring of AM metals challenging. Frost accretion is a safety hazard in numerous engineering applications. To expand the application of AM, this study experimentally investigates the antifrosting performance of superhydrophobic and slippery lubricant-infused porous surfaces (SLIPSs) generated on AM alloy, AlSi10Mg. By strategically utilizing the subgrain structure in the metallography of the AM alloy, the functionalized superhydrophobic AM surface featuring hierarchical structures was shown to greatly reduce frost formation as compared to functionalized single-tier structured surfaces, hierarchical structures formed on conventional aluminum alloy surfaces, and SLIPSs. Optical observation of frost propagation demonstrated that the mechanism of frost delay is governed by the inhibition of spontaneous droplet freezing through exceptional Cassie state stability during condensation frosting. The Cassie stability results from the unique AM structure morphology, which creates a higher structural energy barrier to prevent condensate from infiltrating the cavities. This phenomenon also enables the formation of a high surface-to-droplet thermal resistance, which eliminates spontaneous droplet freezing down to a -15 °C surface temperature. Our work demonstrates a scalable structuring method for AM metals, which can result in delayed frost formation, and it also provides guidelines for the development of engineered surfaces requiring the antifrosting function for several industries.